Overarticulator on Contoid [r] Indonesian Deaf Children - Abu Darim; Bambang Yulianto; Nuryadi Nuryadi; Lis Setyowati; Etty Widawati; Kurniawati Kurniawati (Journal of Applied Science, Engineering, Technology, and Education, 2019)
This research aims at describing overarticulator contoid [r] deaf children Indonesia. This research uses the qualitative descriptive method. Data researched is overartikulator contoid [r] deaf children. The source of data is the son of deaf SLB-B on kindergarten groups A deaf bit heavy. Data collection is done with the data source mimicked speech researcher and teacher or when pronouncing vocabulary list Containing contoid [r]. The collection of data using techniques of natural observation, observation, participation, of a scheduled Fishing fishing substitution, recording, record-keeping, and field. Data analysis using the method in accordance with the technique of determining element is broken. Based on data analysis, contoid [r] resulting in two groups of deaf children. The Union, contoid [r] generated anyway. [r], [«r«r], [arer], [rr], [l], [ll], [«l], [l«], and [et]. Second, contoid [r] produced change. In two of the group, contoid [r] created by [r], [ The results contain the differences distinguishing characteristic on the basis of the representation and the representation of contoid phonetic [r]. In the difference that happens overarticulator contoid [r] which does not occur on other contoids. From an overarticulator, it changes the sounds anaptiksis, reduplication, and contoid attenuation [r].